2021
DOI: 10.3389/fphar.2021.639651
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plant-Derived Natural Compounds in Experimental Autoimmune Encephalomyelitis: A Review of the Treatment Potential and Development Strategy

Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system that is mainly mediated by pathological T-cells. Experimental autoimmune encephalomyelitis (EAE) is a well-known animal model of MS that is used to study the underlying mechanism and offers a theoretical basis for developing a novel therapy for MS. Good therapeutic effects have been observed after the administration of natural compounds and their derivatives as treatments for EAE. However, there has been a severe lag in the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 184 publications
(238 reference statements)
0
3
0
Order By: Relevance
“…Many reviews have summarized the results of using NPs for treating PD, MS, or other neurodegenerative diseases according to their molecular structures (34,(38)(39)(40)(41)(42)(43)(44). To our knowledge, few categorized based on their functions toward cellular and subcellar processes inherent in both PD and MS. No reviews have linked the use of NPs for PD to those utilizing the same or similar type of NPs as MS modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews have summarized the results of using NPs for treating PD, MS, or other neurodegenerative diseases according to their molecular structures (34,(38)(39)(40)(41)(42)(43)(44). To our knowledge, few categorized based on their functions toward cellular and subcellar processes inherent in both PD and MS. No reviews have linked the use of NPs for PD to those utilizing the same or similar type of NPs as MS modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Naringenin compound has improved Alzheimer’s disease, Type 2 Diabetes, and Cancer in several clinical trials studies [ 20 22 ]. Experiments were carried out by incorporating 5% Naringenin compound into mice’s diets or injecting 20–80 mg/kg of Naringenin compound had immunomodulatory effects and could regulate T-regs and balance the Th1/Th2 ratio in autoimmune arthritis, resulting in less inflammation [ 23 25 ]. Also, growing evidence has been shown that the Hesperetin compound had neuroprotective properties in experimental models of neurodegenerative disorders [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mey., is one of the protopanaxadiol (PPD)-type ginsenosides, while the proportion of ginsenoside Rd in ginseng is very low ( Liu et al, 2020a ). Interestingly, the promising effects of the pretreatment and treatment of ginsenoside Rd on neurological diseases, cancer, gastrointestinal disease, and metabolic diseases have been studied extensively in in vivo and in vitro models ( Guo et al, 2021 ; Chen et al, 2022 ; Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%